2014
DOI: 10.5812/ircmj.13375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Family-Centered Empowerment Model Based Education Program on Quality of Life in Methamphetamine Users and Their Families

Abstract: Background:Nowadays there are more concerns about drug treatment of methamphetamine abusers whereas quality of life (QOL) related supportive psychotherapy is less credited.Objectives:This study aimed to evaluate the effects of family-centered empowerment model on social support and QOL of methamphetamine users and their families.Patients and Methods:This study was a randomized clinical trial; individuals were randomly allocated to three groups: a group for educating methamphetamine users in recovery (95 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
10
0
7
Order By: Relevance
“…The study by Nassehi et al (2014) with an aim to investigate the effect of family-based empowerment program on patients with asthma indicated that total score and quality of life's aspects were significantly different after the intervention when compared to the pretest (13); moreover, the study of Ghasemi et al (2014) showed that an empowerment program made an improvement in the process of patients' social support and quality of life (14). The study of Clary et al (2009) on hemodialysis patents showed that patients' motivation increased after implementing an empowerment program and, also, a considerable increase was observed in self-efficiency, self-esteem and quality of life of patients (15).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Nassehi et al (2014) with an aim to investigate the effect of family-based empowerment program on patients with asthma indicated that total score and quality of life's aspects were significantly different after the intervention when compared to the pretest (13); moreover, the study of Ghasemi et al (2014) showed that an empowerment program made an improvement in the process of patients' social support and quality of life (14). The study of Clary et al (2009) on hemodialysis patents showed that patients' motivation increased after implementing an empowerment program and, also, a considerable increase was observed in self-efficiency, self-esteem and quality of life of patients (15).…”
Section: Introductionmentioning
confidence: 99%
“…(Marcon, Rubira, Espinosa, Belasco, et al, 2012). Observou-se que prevaleceram familiares do sexo feminino (98%), dado que corrobora com estudo feito em um CAPS -ad no Estado de Mato Grosso e Irã, em que 90,8% e 61,1% eram mulheres respectivamente (Ghasemi et al, 2014;. Esses dados mostram o impacto do uso de drogas na família e principalmente na saúde da mulher.…”
Section: Resultsunclassified
“…Muitas vezes, mesmo com um emprego fora do lar, a mulher assume esse papel, o que repercute na redução do tempo livre e traz implicações para a sua vida (Pereira et al, 2013). Enquanto a mulher (mãe) é a cuidadora, os outros familiares tornam-se dependentes desse cuidado, gerando um padrão disfuncional na relação familiar, que centraliza toda a sobrecarga do cuidado na mãe produzindo estresse e frustações (Ghasemi et al, 2014;Moreira et al, 2013;Vasconcellos & Prati, 2013) Nesse estudo, a maioria dos familiares era casado e inserido no mercado de trabalho.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Three questionnaires were used for data collection: 1) the Medical Outcome Study Short Form-36 (SF-36); 2) PBC-40; and 3) PBC-27. The Medical Outcomes Study Short Form 36 (SF-36) is a widely used and validated generic questionnaire to measure HRQoL in various populations with a wide variety of medical conditions ( 8 , 9 ). The disease-specific instruments, PBC-40 and PBC-27 assess the symptoms of chronic cholestasis such as fatigue, excessive daytime sleepiness, pruritus and impaired memory and concentration ( 3 , 4 ).…”
Section: Methodsmentioning
confidence: 99%